PEMAHAMAN DAN PENGGUNAAN VARIASI BAHASA PRANCIS BIDANG AGROWISATA BAGI STAKEHOLDER PARIWISATA DI MAKASSAR SEBAGAI UPAYA PENINGKATAN PELAYANAN KEPADA TURIS MANCANEGARA - Hasyim, Muhammad; Akhmar, Andi Muhammad; Kuswarini, Prasuri; Masdiana, Masdiana (JURNAL ILMU BUDAYA, 2018)
The monetary crisis since 1998 that hit Indonesia, has a negative impact on the tourism business, which is marked by a decrease in the number of foreign tourist visits that have an impact on tourism economic activities. On that basis, in 2018 the Indonesian government has emphasized the importance of empowering existing natural potential and becoming a regional characteristic as a potential tourism activity. One of the programs launched by the area in Toraja is the improvement and management of agrotourism (agrotourism) with the image of the Toraja region, as the Coffee Regency. Based on the results of the research, one solution was found, namely the need for a variant of a tourist attraction that supports the main tourist attractions of Toraja, Tradition Culture (graves) and Tongkonan traditional houses. The potential variation of objects to be developed in Toraja is agrotourism which so far has not been fully developed. In developing agrotourism in Toraja, it is important to improve services from aspects of specific field languages (agrotourism), one of which is French. For this reason, the solution that can be given to tourism stakeholders is to provide language skills training through understanding and using French variants in agro-tourism. The results of this workshop show that participants are able to explain vocabulary and speak (communicate orally) in French in the field of agrotourism